PERANCANCANGAN MEDIA PEMBELAJARAN PADA PAUD BINA KELUARGA BALITA HOLISTIK INTEGRATIF AL LESHA BINUANG MENGGUNAKAN MACROMEDIA FLASH 8 - Rahmat Rahmat; Iqbal Fernando; Desi Yuliasari (LPPM Universitas Bina Bangsa, 2022)
Multimedia is made to support learning so that the situation becomes more conducive. A group of images that are arranged in an orderly manner and follow the flow of movement and are defined as moving visuals is called animation. This study aims to analyze and determine multimedia learning compared to the previous method. And to produce learning media using Adobe Flash. In building a learning media that uses Adobe Flash, the Action Script programming language is used to manage it. The end result of this research is to design learning media that uses Adobe Flash. Which will make it easier for the teacher to convey the material. Based on the conclusions of this study, it is the result of designing learning media at the Holistic Integrative Binang Toddler Family Development Early Childhood Education Center, learning media is intended to make it easier for teachers to convey material and students understand easily